NTR (Encyclopedia of Signaling Molecules, 2018)
Introduction Nicotine-free ("zero-nicotine") vaping devices are marketed as alternatives to nicotine, yet their promotion with flavors and claims of non-addictiveness raise concerns for tobacco regulatory science. Such marketing may encourage youth initiation, transition to nicotine vaping, or co-use with nicotine or other substances. Little is known about these products' marketing and perceptions on social media popular among youth. This study examined marketing claims of zero-nicotine products and user reactions on TikTok. Methods We conducted a qualitative content analysis of 435 TikTok promotional videos (July 2023-July 2024) posted by five zero-nicotine brands. Videos were inductively coded to identify themes. User comments (N = 5,418) were analyzed using latent Dirichlet allocation (LDA) topic modeling and Valence Aware Dictionary and sEntiment Reasoner (VADER) sentiment analysis. Results Among promotional videos featuring zero-nicotine products, 48% were entertaining, 39% discussed quitting nicotine, 38% portrayed zero-nicotine products as a healthier alternative to nicotine vaping or smoking, and 26% included unverified or misleading claims about health benefits. Flavors appeared in 34% of videos, taste comparisons in 20%, and "natural ingredients" in 15%. LDA-detected themes in comments revealed mixed reactions: difficulties quitting nicotine, concerns about health effects of zero-nicotine products, and skepticism about their cessation effectiveness, alongside curiosity and interest in trying zero-nicotine products and their lower-risk perceptions, including among self-identified minors. Conclusions Zero-nicotine products, though marketed for adult cessation, are promoted on TikTok with youth-appealing features alongside reduced harm messages. Findings highlight youth appeal, misperceptions of safety, and the need for research and regulatory attention to zero-nicotine products.